HLA-G: An Important Mediator of Maternal-Fetal Immune-Tolerance - Zhuang, Baimei; Shang, Jin; Yao, Yuanqing (Frontiers in Immunology, 2021)
Maternal-fetal immune-tolerance occurs throughout the whole gestational trimester, thus a mother can accept a genetically distinct fetus without immunological aggressive behavior. HLA-G, one of the non-classical HLA class I molecules, is restricted-expression at extravillous trophoblast. It can concordantly interact with various kinds of receptors mounted on maternally immune cells residing in the uterus (e.g. CD4+ T cells, CD8+ T cells, natural killer cells, macrophages, and dendritic cells) for maintaining immune homeostasis of the maternal-fetus interface. HLA-G is widely regarded as the pivotal protective factor for successful pregnancies. In the past 20 years, researches associated with HLA-G have been continually published. Indeed, HLA-G plays a mysterious role in the mechanism of maternal-fetal immune-tolerance. It can also be ectopically expressed on tumor cells, infected sites and other pathologic microenvironments to confer a significant local tolerance. Understanding the characteristics of HLA-G in immunologic tolerance is not only beneficial for pathological pregnancy, but also helpful to the therapy of other immune-related diseases, such as organ transplant rejection, tumor migration, and autoimmune disease. In this review, we describe the biological properties of HLA-G, then summarize our understanding of the mechanisms of fetomaternal immunologic tolerance and the difference from transplant tolerance. Furthermore, we will discuss how HLA-G contributes to the tolerogenic microenvironment during pregnancy. Finally, we hope to find some new aspects of HLA-G in fundamental research or clinical application for the future.